INNOVATIONS IN ELECTRONICS FOR DETECTING OBJECTS IN SURFACE LAYERS OF SOIL: A REVIEW OF METHODS AND DIRECTIONS FOR FURTHER IMPROVEMENT - ВІНТОНЯК, ВІТАЛІЙ (Technologies and Engineering, 2024)
Purpose. The research in this publication reveals a comprehensive analysis of modern electronic technologies for detecting objects in the surface layers of the ground, assessing their efficiency and accuracy, and identifying promising areas for further innovation and research in this area. Methodology. To achieve the research objectives, the theoretical analysis of scientific literature, as well as methods of analyzing and summarizing existing data were used. The main research tools were a comparative analysis and classification of the methods used to detect objects in the surface layers of the ground. The solution of scientific problems was carried out using a systematic approach to the selection of materials, the use of inductive and logical analysis, and observation methods to analyze information obtained from the literature. Findings. The study analyzed the main technologies for detecting objects in the upper layers of the ground: ground penetrating radar (GPR), metal detectors, laser Doppler vibrometry, magnetometry, and optical methods. It was found that the combination of different technologies can significantly improve the accuracy and efficiency of object detection. This work also highlighted the potential of applying machine learning to improve object classification and reduce false positives. Further, it was found that reducing the weight and power consumption of detection systems can facilitate their use on unmanned vehicles, which opens up new prospects for the use of these technologies in remote monitoring and exploration of hard-to-reach areas. Originality. This paper is the first to systematize and analyze in detail the existing technologies for detecting objects in the upper layers of the ground, including GPR, metal detectors, laser vibrometry, magnetometry, and optical methods, based on criteria such as detection depth, equipment cost, and the possibility of integration with other systems. This comprehensive approach allows us to identify white spots in current research and identify areas for further development of each method, including improving accuracy, reducing power consumption and weight of devices for more efficient use on UAVs and ground operations. Practical value. Comparison results of such electronic technologies as GPR, metal detectors, laser vibrometry, multispectral imaging have been obtained. The current trends in the development of these technologies and opportunities for further research have been identified.